Interreligious Interaction in a Multicultural Society (Case Study: About Tolerance and Harmony in Indonesia) - Slamet Pamuji (Journal of Noesantara Islamic Studies, 2024)
This research aims to analyze forms of tolerance and harmony between religious believers in multicultural society in Indonesia. The method used is a qualitative method, data is obtained through data collection, observation and document analysis. The research results show that religious education has a significant role in forming inclusive attitudes and reducing the potential for religious conflict. Apart from the diversity and multiculturalism of society in Indonesia, it can be maintained thanks to the existence of the Pancasila ideology as a unifying ideology for the nation. The forms of tolerance and harmony between religious believers in multicultural society in Indonesia include: dialogue between religions and ethnicities and cooperation between religious believers; believe in one's own religion and respect other people's religions; and Interfaith Communication Interaction.